Reviving the past to protect the future: developing a social-ecological clam garden site selection model - Courtney M. Greiner (4694470) (2025)
The tightly coupled social-ecological nature of fisheries calls for science and management to work in tandem across knowledge systems to address the complex issues impacting fisheries productivity and associated benefit flows. However, the pragmatics of how to accomplish this in an equitable manner are rarely discussed. In this paper we provide a real-world example of how to effectively and meaningfully weave ecological and social sciences with diverse knowledge and ways of knowing in order to revive an ancient Indigenous aquaculture practice to address climate-related resource management and community health concerns. Specifically, we present the detailed steps of our transdisciplinary clam garden site selection process: 1) create Technical Advisory Group, 2) develop initial exclusion map, 3) collect ecological data and conduct multi-criteria decision analysis, 4) collect socio-cultural data, and 5) select a site. Our methodical, stepwise framework included collaborative management through community participation and decision-making, and utilization of multiple perspectives. This resulted in a transparent, inclusive process that garnered community support and increased the likelihood for successful implementation. Our work is specific to the Swinomish Indian Tribal Community; however, the process can be adapted to address the place-based needs and values of other coastal communities. • Indigenous aquaculture practice addresses socio-ecological climate concerns. • Transdisciplinary framework uses diverse knowledge systems. • Real-world example of novel social-ecological site selection process. • Community participation in decision-making increases likelihood of success. • Process is adaptable to meet the needs and values of other communities. Indigenous aquaculture practice addresses socio-ecological climate concerns. Transdisciplinary framework uses diverse knowledge systems. Real-world example of novel social-ecological site selection process. Community participation in decision-making increases likelihood of success. Process is adaptable to meet the needs and values of other communities.